Pelaksanaan Media Gambar Berseri Terhadap Keterampilan Menulis Siswa Kelas IV SDN Pandeanlamper 02 - Fatimah, Nurulul (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Learning Indonesian has one skill, namely writing. Writing skills material is a travel report. In reality, students in writing travel reports could not reach KKM scores, especially at SDN Pandeanlamper 02 Semarang. This attracts researchers to find out how to improve writing skills at the elementary school level in grade IV. This attracts researchers to find out how to improve writing skills at the elementary school level in grade IV. This study uses quantitative research with experimental research taking the population of all students in the class totaling 27 students. Data collection using the test method. The results of the study showed that there was an increase in student learning outcomes, which was originally only 36.50% to 100%. Thus, it can be concluded that using serial images can improve the writing skills of grade IV students' travel reports.